A Review on Solution‐Processable Dopant‐Free Small Molecules as Hole‐Transporting Materials for Efficient Perovskite Solar Cells. Issue 9 (18th June 2020) - Zhang, Luozheng; Zhou, Xianyong; Liu, Chang; Wang, Xingzhu; Xu, Baomin
Abstract: Perovskite solar cells (PSCs) based on conventional hole‐transporting materials (HTMs) have achieved power conversion efficiencies comparable to those of typical inorganic solar cells; however, the dopants used to increase the hole mobility or the film‐forming ability impart these devices with a poor long‐term stability, blocking the industrial commercialization of PSCs. As an alternative, HTMs without any dopants are explored. Herein, dopant‐free small molecular HTMs (SM‐HTMs) are reviewed and the performance based on the analyses of their molecular structures are evaluated. A summary of the designing principle and an outlook of the development of highly efficient SM‐HTMs are presented. Abstract : Herein, dopant‐free small molecular hole‐transporting materials (SM‐HTMs) for perovskite solar cells with efficiencies of over 15% are reviewed, categorized according to their molecular structures rather than the device configurations and the molecular structures are related with their properties. A future researching direction is also provided on how to design efficient SM‐HTMs.